Propensão ao vínculo com a organização: desenvolvimento do conceito, proposta de instrumentos e análise do seu impacto sobre os vínculos construídos após o ingresso do indivíduo na organização - Balsan, Laércio André Gassen (2017)
Although the research about Organizational Commitment is still heavily dominated by the three-dimensional model of Meyer and Allen (1991), a current agenda designing new constructors with the goal of ceasing a redundancy and conceptual overlap, as well as delineate as behavioral attitudes characteristic of complex commitments, that came to be considered as separate links. In spite of such evolution, little is known until now about the propensity of a individual to develop a certain bond. There are specifically a few theoretical reflections about the propensity to commitment and a first measurement attempt, which has been criticized. Beyond commitment, the individual's tendency to entrench and/or to consent has not yet received any theoretical insight, neither empirical attempts at evaluation. As we are faced with a novelty in the area, any initiative to think in what way workers would have a propensity to develop the bond of commitment, entrenchment and/or consent with the organization is fundamental, since the real bond can‟t exist before the individual's entry into the organization and therefore can‟t be measured prior to joining the organization. Inserted in this concern, this thesis is composed by a theoretical study and four empirical studies. In the first article of theoretical nature, the aim was to present the fundamentals and conceptualize the propensity to the different links, proposing a framework whose process of developing the bonds begins before the worker joins the organization. The three other articles, eminently empirical, present three new scales: the Organizational Commitment Propensity Scale (EPCO), the Organizational Entrenchment Propensity Scale (EPENT) and the Organizational Consent Propensity Scale (EPCON). All measures developed showed good adjustment indexes and adequate psychometric parameters. Finally, the last article tested the predictive power of these scales on future bonds. For this purpose, a longitudinal study was carried out, consisting of two data collections: one before the individual entered the work environment and another one nine months after starting their new job. The results show that the workers entering the organization already have a tendency to develop a certain bond, which is determinant of the future linkage. The results found in the present thesis are unprecedented, and as the research in the area advances, there will be more evidence about the propensity and its implications for performance at work, with consequences for the individual and for the organization. Knowing in beforehand such tendency, it may direct the company to hire the individuals most predisposed to develop the link advocated by it. It will also guide the management of people to actions that minimize the negative potential of certain bonds and ensure greater attachment and pro activity from the first days of work. Since they are new concepts, much conceptual and empirical work must be undertaken. Methodological strategies used here can be retaken for contributing to a greater theoretical advances and practical applications of the proposed framework, also improving the scales and verification of the effect of the personal characteristics and previous experiences on the Propensity to Organizational Commitment, Entrenchment and Consent.